Effect of interaction of Xanthomonas axonopodis pv. betli cola and Pseudomonas betle on the extent of lesion develop ment on betelvine leaf (The Journal of Plant Protection Sciences, 2024)
Betelvine (Piper betle L.) is an important cash  crop in West Bengal, India. This crop is com monly affected by stem rot and leaf spot dis ease (4) caused by two different genera of  bacteria - Xanthomonas axonopodis pv. betli cola Patel et al. (Vauterin et al.) and Pseudo monas betle Ragunathan (Săvulescu). Two  bacterial pathogens enter into the host through  stomata, hydathode and injury. Both the bac teria produce prominent dark brown lesions at  any portion of the vine stem. Surface of such  lesion becomes sticky in humid condition. On the leaf, small to large, circular to irregu lar and/or angular brown coloured spots and  marginal leaf blight symptoms are produced  by both the bacteria. All types of spots are  surrounded by yellow halo or the halo is pre sent in between brown and green tissue. At  the underside of the leaf, the brown lesion is  encircled by a water soaked zone or water  soaked area which is found in between brown  lesion and green tissue in marginal blight.  Frequently both the bacteria have been de tected from the same leaf spot or stem lesion  (3, 4) in different plantation. This fact created  an interest to find out whether the interaction  of the two bacteria had any effect on the size  of lesion.  Leaves of betelvine (cv. Bangla Pan) were  collected from farmers' Boroj. Bacterial sus pension was prepared by adding sterile dis tilled water in the tube containing 48 hrs old  slant culture of the bacteria. The tube was  properly shaken to form uniform suspension  (109 cell/ml). Afterwards, with the help of a  hypodermic syringe, the bacterial suspension  was injected in the veins of betel leaves (6).  Upon injection, the leaf tissue adjacent to the  injected vein became water soaked. The in oculated leaves were kept in polypropylene  bags containing a moist cotton wool. After  blowing air into the bags, the mouth of the  bag tied with a rubber band. These polypro pylene bags were then incubated at 28 ± 1°C  in BOD incubator.
Keywords: Xanthomonas axonopodis pv. betlicola and Pseudomonas betle; tissue; lanacearum